THE COST CONUNDRUM: NAVIGATING DISCUSSIONS AROUND COST FOR HEART FAILURE MEDICATIONS. (11th November 2018) - Finnigan-Fox, G; Allen, L; Matlock, D; Jenkins, A
Abstract: Navigating the pharmaceutical market can be particularly cumbersome/difficult for older patients on fixed incomes seeking relief from their heart failure symptoms. We developed a patient decision aid (PtDA) explaining the differences of traditional vasodilators (ACE-Inhibitors and ARBs) used to treat heart failure versus a new, more effective but costly medication (the ARNI sacubitiril/valsartan). Feedback was gathered from key stakeholders (patients, physicians, and the manufacturer) in order to iteratively develop the PtDA. Qualitative methods included in-depth, semi-structured interviews and informal focus groups. Participants included 13 patients, 10 physicians and the pharmaceutical company. This study was conducted in the University of Colorado Health Care System. Feedback from all parties overwhelmingly focused on cost. However, there were distinct differences in how cost information should be discussed. Patients indicated that cost information was crucial; even patients that could comfortably afford the medication empathized that cost may be a barrier to patients. Physicians and the manufacturer were distinctly less comfortable with the cost discussion, expressing that cost should be a secondary factor for patients when considering switching to the ARNI. Although cost was the only drawback for switching to the ARNI, inclusion of information around cost in the PtDA was controversial. Patients desired information on cost, citing it as a critical factor in their decision-making process; physicians and the manufacturer felt that, by including cost information, the benefits (i.e., lower mortality and hospitalization) were lost. This suggests a schism between how providers and their patients view treatment decisions that are grounded in cost.